2021
DOI: 10.1007/s12144-021-02374-3
|View full text |Cite
|
Sign up to set email alerts
|

Cyberloafing behaviors among university students: Their relationships with positive and negative affect

Abstract: With the technological advances, the use of digital devices, such as laptops, tablets, or smartphones in the educational setting has become prevalent among young people. Accordingly, there has been an increased concern among scholars on students’ in-class Internet use for personal purposes; namely, ‘cyberloafing’. Considerable research has demonstrated the adverse effects of in-class Internet use on students’ learning environment and academic performance. The present study particularly investigates the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 96 publications
(164 reference statements)
3
14
0
1
Order By: Relevance
“…Smartphones located in the bag and outside the room influenced students' concentration on the task, but this effect did not seem to affect WM. Thus, this study partially supported the findings of Hartmann et al, who showed no evidence of cognitive costs due to smartphone presence in a short-term memory task [9]. Herein, we observed partial correlations among the EEG parameters examined under different smartphone location conditions.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Smartphones located in the bag and outside the room influenced students' concentration on the task, but this effect did not seem to affect WM. Thus, this study partially supported the findings of Hartmann et al, who showed no evidence of cognitive costs due to smartphone presence in a short-term memory task [9]. Herein, we observed partial correlations among the EEG parameters examined under different smartphone location conditions.…”
Section: Resultssupporting
confidence: 91%
“…Despite smartphone-related convenience, smartphone use has raised concerns regarding addiction among university undergraduates. Some studies have suggested a positive effect of smartphone use on learning [8,9]. However, other studies have shown a decrease in academic performance associated with smartphone use [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The present study investigated the secondary school students' cyberloafing behaviours, cognitive absorption, and smartphone addiction levels with considering both the relationship between them and different variables. Although, gender is considered one of the predictors of cyberloafing (Sarıtepeci, 2020;Dursun, Dönmez, & Akbulut, 2018) and males exhibit more cyberloafing behaviour than females (Metin-Orta & Demirtepe-Saygılı, 2021;Sarıtepeci, 2020;Dursun, Dönmez, & Akbulut, 2018;Baturay Toker, 2015;Askew et al, 2014;Garrett & Danziger, 2008), in this study gender is not a significant factor. In the literature, similar findings exist regarding gender effect on cyberloafing behaviour among different student groups; vocational high school students (Gezgin, Arslantaş & Şumuer, 2017), and graduate students (Bağrıaçık Yılmaz, 2017).…”
Section: Discussionmentioning
confidence: 51%
“…The literature review did not reveal any studies examining the direct correlation between cyberloafing behaviors and academic burnout; however, there are some studies that might imply indirect correlations among these variables, which might support the findings of the present study. For instance, there are studies conducted during the COVID-19 pandemic and highlighting that cyberloafing affects academic performances of university students [42,43].…”
Section: Discussionmentioning
confidence: 99%